Cost-effectiveness analysis of camrelizumab plus paclitaxel and carboplatin versus sintilimab plus gemcitabine and cisplatin or carboplatin for the first-line treatment of local advanced or metastatic squamous NSCLC in Chinese mainland - Liu, Xiaoting; Liu, Xiao-xue; Shao, Wenqing; Zhou, Yi; Zhang, Jing; Zhao, Cuirong; Shen, Chengwu (Frontiers in Pharmacology, 2024)
Objective Both camrelizumab plus paclitaxel and carboplatin (CTC) and sintilimab plus gemcitabine and cisplatin or carboplatin (SGP) have been approved by the National Medical Products Administration of China (NMPA) for the first-line treatment of local advanced or metastatic sqNSCLC. However, the comparison of the two treatments as first-line treatments in efficacy or pharmacoeconomics has barely been studied. To deeply understand the costs and outcomes of the two treatments, this work directly compared the cost-effectiveness for the first-line treatment of local advanced or metastatic squamous NSCLC in the Chinese mainland. Methods A network meta-analysis was first performed based on the three clinical trials, namely, CameL-Sq, ORIENT-12, and C-TONG1002, to compare the clinical benefits of the two treatments. The Weibull approximation was applied to further calculate the life expectancy of the two treatments. The partitioned survival model (PSM) was next established, and one-way sensitivity analysis and probabilistic sensitivity analysis were also performed to evaluate the stability of the underlying parameter values and assumptions within the model. Results CTC treatment gained 0.68 QALYs and cost 14,764. SGP treatment gained 0.54 QALYs and cost 14,584. The CTC arm gained 0.14 additional QALYs and cost 179 more than the SGP arm, and the ICERs was 1,269/QALY, which was lower than one-fold GDP per capita in the Chinese mainland (12,734 GDP per capita in 2022). In probabilistic sensitivity analysis, when the WTP ranged from 12,734–38,202 (1–3 folds, 2022 GDP per capita in China), the CTC group had higher probabilities than the SGP group for being cost effective, which ranged from 85.65% to 88.38%. Conclusion From the perspective of the payers, camrelizumab plus chemotherapy was cost-effective compared with sintilimab plus chemotherapy for the first-line treatment of local advanced or metastatic squamous NSCLC in the Chinese mainland.